PENGARUH RELIGIUSITAS DAN PENGETAHUAN AKUNTANSI SYARI’AH TERHADAP MINAT MAHASISWA AKUNTANSI BERKARIR DI LEMBAGA KEUANGAN SYARI’AH - Ibrahim, Ibrahim; Hala, Yusriadi; Agus, Rosida Maedina (Universitas Patria Artha, 2022)
This study aims to determine whether religiosity and knowledge of sharia accounting have an effect on the interest of accounting students to have a career in sharia financial institutions. Collecting data using primary data obtained from questionnaires using a purposive sampling method. The population is accounting students at STIEM Bongaya Makassar with a total sample of 114 respondents. The data quality test used in this study is the validity of the Pearson correlation and the reliability of Cronbach's Alpha. The classical assumptions have also been tested in the form of normality assumptions, multicollinearity assumptions and heteroscedasticity assumptions. The method of data analysis used multiple linear regression techniques. The results of this study indicate that the religiosity variable (X1) has no significant effect on the interest of accounting students to have a career in Islamic financial institutions because the significant value of t 0.098 is greater than = 0.05. The Islamic accounting knowledge variable (X2) has a significant effect on the interest of accounting students to have a career in Islamic financial institutions because the significant value of t 0.00 is smaller than = 0.05.